Multifactorial Model Of Attitudes Towards Appearance: Empirical Investigations - Labunskaya, Vera (Տիգրան Մեծ)
This study is focusing on interrelations between attitudes towards Appearance (AP), value functional significance of AP, and life satisfaction. The study is aimed at gaining a theoretical foundation of the developed Multifactorial Model of Attitudes towards AP as well as at empirical testing of the interrelations between the single factors of the model and their combined influence on life satisfaction. It is hypothesised that a different combination of the single factors of the Multifactorial Model of Attitudes towards AP has a different impact on life satisfaction. The participants were 86 females and 86 males aged between 17 and 25 years. The inventory “Diagnostics of Real Structure of Personality Value Orientations” (Bubnova, 1999) the questionnaires “Significance of AP in Various Life Situations” (Labunskaya & Serikov, 2018), Attitudes towards AP, Satisfaction and Concern” (Labunskaya & Kapitanova, 2016), the AP Perfectionism Scale (APPS) (Srivastava, 2009) and the Life Satisfaction Index developed by Neugarten and adopted by N. V. Panina (1993) were administered. The factorial analysis revealed two types of interrelations that relate to different components of the developed Multifactorial Model of Attitudes towards AP. The results showed that considering AP as a value, attributing of higher significance to AP in various interaction contexts as well as higher AP perfectionism lead to lower life satisfaction.
Keywords: Psychology